Resolver Problemas :uma educação para a ação : caracterizando os modelos mentais usados na resolução de problemas não convencionais - Pais, Rosemary Barbeito (2006)
This study arose from a concern as for the difficulty that many children present in solving math word problems, even when they dominate the use of algorithms. It was taken as the main point that the presence of the native language in the heading of the word problems might contribute to this difficulty. In this way, the word problems that were used in this study emphasized the native language so that it would be possible to observe the mental models used by 4th graders during the problem solving stage. The information was gathered from the written registration of the solutions to the problems, from the spontaneous dialogs of the students, which were transcribed from audio recordings of the dialogs of the groups during the problem solving stage; and the ve rbal reactions caused as a result of the interview done by the researcher after the problem had been solved. Having the analysis of this data as a basis, categories were created which intended to explain the mental models used by the students during the problem solving process. It is possible to conclude that both the arithmetic and the native language overlap during the solving of the situational problems; however there are moments in which one or the other becomes more relevant. The arithmetic thinking is seen as the most important during the problem solving process, but the mother language becomes relevant, especially when the student does not promptly elaborate a hypothesis of arithmetic solution, or when this hypothesis is unsatisfactory. It was also possible to notice that the pictorial representation is also used by the students as a resource to solve the problems.